The Selection and Causal Effects of Work Incentives on Labor Productivity: Evidence from a Two-Stage Randomized Controlled Trial in Malawi - Hyuncheol Bryant Kim; Seonghoon Kim; Thomas T. Kim (Institute of Labor Economics (IZA), 2017)
Incentives are essential to promote labor productivity. We implemented a two-stage field experiment to measure effects of career and wage incentives on productivity through self-selection and causal effect channels. First, workers were hired with either career or wage incentives. After employment, a random half of workers with career incentives received wage incentives and a random half of workers with wage incentives received career incentives. We find that career incentives attract higher-performing workers than wage incentives but do not increase productivity for existing workers. Instead, wage incentives increase productivity for existing workers. Observable characteristics are limited in explaining the selection effect.
Keywords: J30; O15; M52; 330; career incentive; wage incentive; internship; self-selection; labor productivity